Public Health Ethics: Cases Spanning the Globe - H. Barrett, Drue; W. Ortmann, Leonard; Dawson, Angus; Saenz, Carla; Reis, Andreas; Bolan, Gail (Public Health Ethics Analysis,, 2016)
This book is open access, which means that you have free and unlimited access. This book highlights the ethical issues and dilemmas that arise in the practice of public health. It is also a tool to support instruction, debate, and dialogue regarding public health ethics. Although the practice of public health has always included consideration of ethical issues, the field of public health ethics as a discipline is a relatively new and emerging area. There are few practical training resources for public health practitioners, especially resources which include discussion of realistic cases which are likely to arise in the practice of public health. This work discusses these issues on a case to case basis and helps create awareness and understanding of the ethics of public health care. The main audience for the casebook is public health practitioners, including front-line workers, field epidemiology trainers and trainees, managers, planners, and decision makers who have an interest in learning about how to integrate ethical analysis into their day to day public health practice. The casebook is also useful to schools of public health and public health students as well as to academic ethicists who can use the book to teach public health ethics and distinguish it from clinical and research ethics. .